Short Films from a Small Nation Danish Informational Cinema 1935-1965 - Thomson, C. Claire (Edinburgh University Press, 2022)
The first book-length study in English of a national corpus of state-sponsored informational filmFor three decades, state-sponsored short filmmaking educated Danish citizens, promoted Denmark to the world, and shaped the careers of renowned directors like Carl Th. Dreyer. The first book-length study in English of a national corpus of state-sponsored informational film, this book traces how Danish shorts on topics including social welfare, industry, art and architecture were commissioned, funded, produced and reviewed from the inter-war period to the 1960s. Examining the life cycle of a representative selection of films, and discussing their preservation and mediation in the digital age, this book presents a detailed case study of how informational cinema is shaped by, and indeed shapes, its cultural, political and technological contexts.Key featuresCombines close textual analysis of a broad range of films with detailed accounts of their commissioning, production, distribution and reception in Denmark and abroadConsiders a broad range of genres and sub-genres, including industrial process films, public information films, art films, the city symphony, the essay film, and many moreMaps international networks of informational and documentary films in the post-war periodExplores the role of informational film in Danish cultural and political history Access additional resources on the Danish Film Institute websiteClaire Thomson discusses Danish public information films on the BBC podcast
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Apr 2022)
Keywords: Film, Media & Cultural Studies; PERFORMING ARTS / Film & Video / General; Instructional films -- Denmark; Motion pictures -- Denmark; Short films -- Denmark